COMMUNICATION STRATEGY OF THE NORTH SUMATRA PROVINCE COMMUNICATION AND INFORMATICS DEPARTMENT IN IMPROVING THE PUBLIC INFORMATION OPENNESS INDEX IN THE ERA OF DIGITAL DISRUPTIONS - Adiva Amanda; Muaz Tanjung (Program Pascasarjana UIN Sumatera Utara, 2026)
The era of digital disruption has transformed patterns of public communication while simultaneously creating new challenges for information openness, particularly the rise of disinformation, the acceleration of information flows, and growing public demands for fast and accessible services. In this context, the Communication and Informatics Office of North Sumatra Province plays a strategic role as the manager of public communication and the main Information and Documentation Management Officer (PPID) at the provincial level. This study aims to analyze the communication strategy of the North Sumatra Provincial Communication and Informatics Office in improving the Public Information Openness Index (IKIP) in the era of digital disruption. This study employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observation, and documentation, using primary data from structural officials and related implementers, as well as secondary data from institutional documents and official sources. Data analysis was conducted through the stages of data condensation, data display, and conclusion drawing and verification. The findings show that the communication strategy emphasized the digitalization of public information services through an integrated online one-stop system, the strengthening of Open Data Sumut, metadata-based information management, multichannel public communication, and a more human-centered and responsive narrative approach. However, the implementation of this strategy still faces several challenges, including the gap between bureaucratic procedures and digital public expectations, inter-agency consistency, and local political dynamics that affect IKIP achievement. This study concludes that improving public information openness in the digital era requires the integration of technological innovation, legal certainty, and adaptive two-way public communication